2017
DOI: 10.1002/jcb.26416
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐1 receptor‐associated kinase 1 correlates with metastasis and invasion in endometrial carcinoma

Abstract: Endometrial carcinoma (EC) is one of the most common malignancies in the world. Previous studies have investigated the altered expression of interleukin-1 receptor-associated kinase 1 (IRAK1) in various cancers. We aimed at exploring the biological function and the underlying molecular mechanism of IRAK1 in EC. In this study, IRAK1 was found elevated in EC compared with normal tissues. Further, high IRAK1 expression level was correlated with higher tumor stage, lymph node metastasis, myometrial invasion, and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…AURKB plays a central role in mitosis and participates in the division of cells from G2 phase to M phase [ 25 , 26 ]. The expression of the mitotic cell cycle (CDK1) was significantly suppressed by IRAK1 knockdown [ 27 ]. In UCEC, ZBTB7A may regulate cell cycle progression via interacted kinases.…”
Section: Disscusionmentioning
confidence: 99%
“…AURKB plays a central role in mitosis and participates in the division of cells from G2 phase to M phase [ 25 , 26 ]. The expression of the mitotic cell cycle (CDK1) was significantly suppressed by IRAK1 knockdown [ 27 ]. In UCEC, ZBTB7A may regulate cell cycle progression via interacted kinases.…”
Section: Disscusionmentioning
confidence: 99%
“…IL-1 involvement is also implicated in some gynecologic cancers; in endometrial cancer (EC) IL-1R-associated kinase 1 (IRAK1) expression was shown to be elevated in EC compared with normal tissues, correlating with worse staging, metastasis, invasiveness, and low survival rate [ 74 ]. IL-1β/IL-1RI expression was found to be elevated in both cancer epithelial and stromal cells in samples from ovarian cancer patients, leading to repression of p53 tumor suppressor and correlated with reduced overall survival [ 75 ].…”
Section: Il-1 Dysregulation and Its Contribution To Cancer And Tumorimentioning
confidence: 99%
“…A panel of cell-cycle-associated genes was derived from the KEGG pathway database ( http://www.kegg.jp/kegg/ ), as previously described [ 14 ]. In total, 124 genes were listed; however, mRNA expression data of genes MYC and CCND1 were unobtainable, and the remaining 122 candidate genes were analyzed (Additional file 1 : Table S1).…”
Section: Methodsmentioning
confidence: 99%